An animal-type Na+/K+-ATPase, PhNKA2, is involved in the salt tolerance of the intertidal macroalga Pyropia haitanensis - Feng, Rongrong; Chen, Qi; Xu, Yan; Ji, Dehua; Xie, Chaotian; Wang, Wenlei (Frontiers in Plant Science, 2025)
Intertidal red algae, are more tolerant to salt stress than terrestrial plants, contain a Na+ transporter (Na+/K+-ATPase) that is homologous to animal Na+/K+-ATPases. Although two Na+/K+ pump genes from Pyropia/Porphyra were cloned and their differential expression patterns under salt stress were analyzed, the regulatory mechanism of Na+/K+-ATPase genes in Na+ expulsion and K+ retention process under salt stress remains largely unknown. In this study, we cloned and characterized the animal-type Na+/K+-ATPase gene PhNKA2 in Pyropia haitanensis. The encoded protein was revealed to contain an N-terminal cation-transporting ATPase, E1/E2 ATPase, hydrolase, and a C-terminal cation-transporting ATPase. PhNKA2 was highly conserved in Porphyra/Pyropia. The expression of PhNKA2 in gametophytes was significantly induced by hypersalinity, while there was no obvious change in sporophytes. The heterologous expression of PhNKA2 in Chlamydomonas reinhardtii clearly increased salt tolerance. Na+ efflux and K+ influx were significantly greater in the transgenic C. reinhardtii than in the wild-type control. Furthermore, yeast two-hybrid assays suggested that the interaction between the deubiquitinating enzyme USP5 and PhNKA2 might be critical for the deubiquitination and stabilization of important proteins during the P. haitanensis response to salt stress. The interaction with MSRB2, DHPS, or GDCST may prevent the oxidation of PhNKA2, while actin depolymerization might stimulate Na+/K+-ATPase-dependent membrane trafficking. The results of this study provide new insights into the salt tolerance of intertidal seaweed as well as the underlying molecular basis.